أزمة سد النهضة و تداعياتها على مصر و السودان - بوخرص, غنية (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
يمثل سد النهضة أحد أصعب التحديات التي تواجهها كل من مصر والسودان رغم تشاطرهما تاريخا ومصيرا مشتركا، وبينما تعاني الدولتان تدهورا اقتصاديا وسياسي من عقود تبدأ اثيوبيا مسيرتها التنموية وتسلك سبل توحيد عرقياتها الشديدة التنوع والتناقض على هدف تنموي وسياسي هو مشروع سد الألفية، وعبر ما يقارب عشر سنوات تفاوض وخلال هاته المسيرة الممتدة عرفت كل من مصر والسودان تغيرات كبيرة في أنظمة حكمها، مثلث إثيوبيا طرفا في مفاوضات المرحلة الانتقالية السودانية، وانخرطت القاهرة في محاور مناوئة لها، ولم يتم التوصل إلى توافق حول سد النهضة رغم مسارات التفاوض المتعددة. وتعالج هذه الورقة البحثية خلفيات الأزمة التاريخية واستخدامها في التجاذبات السياسية الداخلية، ومسار التفاوض المباشر (اللقاءات الثنائية والثلاثية)، ومسار الوساطة الدولية عبر الولايات المتحدة والاتحاد الإفريقي وصولا على مرحلة الوساطات الدولية لحل الأزمة على مستوى مجلس الأمن. The Renaissance Dam represents one of the most difficult challenges facing both Egypt and Sudan, despite their sharing a common history and destiny, and while the two countries suffer economic and political decline for decades, Ethiopia begins its development path and takes ways to unite its highly diverse and contradictory ethnicities on a developmental and political goal, which is the Millennium Dam project, and through nearly ten years. Years of negotiation During this extended march, Egypt and Sudan witnessed major changes in their regimes. The Ethiopian triangle is a party to the negotiations of the Sudanese transitional period, and Cairo has engaged in opposing axes, and no consensus has been reached on the Renaissance Dam despite the multiple negotiation tracks. This research paper deals with the backgrounds of the historical crisis and its use in internal political tensions, the path of direct negotiation (bilateral and tripartite meetings), the path of international mediation through the United States and the African Union, and the stage of international mediation to resolve the crisis at the level of the Security Council.